2017
DOI: 10.1007/s40596-017-0714-4
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Peer Mentorship Program to Increase Competence in Clinical Supervision in Clinical Psychology Doctoral Training Programs

Abstract: This program was feasible and acceptable and appears to have had a positive impact on the graduate students who participated. Students reported both high satisfaction with the program as well as an increase in knowledge base and experience in supervision skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…What activities could be part of a supervision practicum experience? In a two-part practicum, students could begin the first section by discussing their own experiences of being a supervisee and then progress to applying generic supervision skills; watching video vignettes from an actual psychotherapy, assessment, and supervision sessions; and group discussions (Bernard & Goodyear, 2014; Falender, & Shafranske, 2012; Foxwell et al, 2017; Newman, 2013; Sharma, 2015). Bearman et al (2013) found that active supervision-training exercises (e.g., instructor modeling, role-playing) predicted higher overall evidence-based practice use in the next therapy session than more passive methods (e.g., discussion).…”
Section: Suboptimal Supervision and Its Implicationsmentioning
confidence: 99%
“…What activities could be part of a supervision practicum experience? In a two-part practicum, students could begin the first section by discussing their own experiences of being a supervisee and then progress to applying generic supervision skills; watching video vignettes from an actual psychotherapy, assessment, and supervision sessions; and group discussions (Bernard & Goodyear, 2014; Falender, & Shafranske, 2012; Foxwell et al, 2017; Newman, 2013; Sharma, 2015). Bearman et al (2013) found that active supervision-training exercises (e.g., instructor modeling, role-playing) predicted higher overall evidence-based practice use in the next therapy session than more passive methods (e.g., discussion).…”
Section: Suboptimal Supervision and Its Implicationsmentioning
confidence: 99%
“…Otros estudios se centran en metodologías de supervisión particulares como la metodología de supervisión entre pares (Foxwell et al, 2017) y el modelo llamado Time-Limited Dynamic Psychotherapy (TLDP) (Anderson et al, 2017), la supervisión Sandtray y la supervisión centrada en soluciones (SFS) (Stark et al, 2015), la metodología Bug-in-the-eye para la supervisión en vivo (Weck et al, 2016), el entrenamiento basado en Internet (IBT) con y sin supervisión (Bender & Dykeman, 2016).…”
Section: Modelos Y Metodologías De Supervisiónunclassified
“…For example, Newman et al (2013) described the application of a structured peer group supervision model utilized in training consultants, which resulted in positive feedback from trainees. Various professional development benefits, such as increased supervision competency and training satisfaction (Foxwell et al, 2017), are associated with providing and receiving peer mentoring. For example, a study evaluating peer mentorship in medical students reported high satisfaction with the mentorship program and increased perceived competency in conducting physical exams and interacting with patients (Choudhury et al, 2014).…”
mentioning
confidence: 99%
“…Further, the focus has been on peer mentoring for therapy supervision (for the peer mentors). Specifically, Foxwell et al (2017) found that their therapy peer-mentoring program was feasibly implemented and well received by peer mentors and mentees, because 90% of participants rated the program as a helpful addition to their training. Additionally, peer mentors reported an increase in their perceived knowledge of supervision and supervisory skills, which were assessed before and after participating in the peer-mentoring program.…”
mentioning
confidence: 99%